Analysis of Characteristics of S45C Steel Changes due to the Quenching and Tempering Process - Golwa, Gian Villany; Romahadi, Dedik; Arwati, I Gusti Ayu (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2022)
S45C steel has a carbon content of 0.50% and its classified as medium carbon steel. The main element content of S45C is carbon (C) is 0.50%, sulphur (S) is 0.035%, and manganese (Mn) is 0.80%. Tempering is a heat treatment process in which the hardening or normalizing process was previously carried out on steel. The research method was carried out where the steel was heated below the critical temperature and cooled. Quenching is a process of rapidly cooling the material from austenitizing from a temperature range of 815 °C to 870 °C for steel. S45C steel was quenched at 950 °C for 120 minutes, then tempered at 700 °C, and 500 °C for 120 minutes. The raw material sample (without heat treatment) is the initial reference standard among the samples undergoing the heat treatment process. They are then analyzed, and the influence and changes in the characteristics after that. In addition, changes in mechanical properties due to the heat treatment process experienced by S45C steel use tensile tests, Charpy impact tests, hardness tests and microstructures. The research results on the quenching process sample were tempered at a temperature of 500 °C and held for 120 minutes, increasing tensile strength by 17.1% and yield strength of 56.82%.